Pengaruh Sektor Pertanian, Kehutanan dan Perikanan, Sektor Jasa Pendidikan, Sektor Jasa Kesehatan dan Kegiatan Sosial, Terhadap PDRB ADHK Kabupaten Kerinci Tahun 2013 – 2022 - Ernita, Dewi; Harahap, Erni Febrina (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to analyze the influence of the agriculture, forestry, and fisheries sectors, the education services sector, the health services sector, and social activities, as well as the construction sector on the Gross Regional Domestic Product (GRDP) Allocation of Funds from Natural Wealth and Constitutional Rights (ADHK) of Kerinci Regency in the period 2013 – 2022 partially and simultaneously. This research evaluates the extent of influence of the agriculture, forestry, and fisheries sectors, the education services sector, the health services and social activities sector, and the construction sector on the PDRB ADHK of Kerinci Regency partially and simultaneously. The research methodology used involves a qualitative descriptive and quantitative descriptive approach. The research results show that there is a positive influence of the agriculture, forestry, and fisheries sectors, the education services sector, the health services and social activities sector, and the construction sector on the PDRB ADHK of Kerinci Regency. This effect reaches 100% simultaneously.